Konsep Pernikahan dalam Islam dan Tantangan Keluarga Modern: Krisis Makna Cinta Sebagai Sumber Konflik Relasional (Jurnal Riset Rumpun Ilmu Sosial, Politik dan Humaniora, 2026)
Changes in values in modern society have led to a shift in the meaning of love in marital relationships, from moral and spiritual commitment to momentary emotions oriented towards personal satisfaction. This shift has weakened long-term commitment and increased relational conflict within families. Islam, with its concept of marriage as mitsāqan ghalīẓā and love as amanah, offers a relevant normative framework to respond to this crisis. This study aims to examine the concept of marriage in Islam and analyze how the values of sakinah, mawaddah, and raḥmah can be solutions to the crisis of the meaning of love in modern families. The method used is a qualitative literature study, through an examination of classical and contemporary Islamic literature and scientific studies on the dynamics of modern families and relationships. The data were analyzed thematically to identify the relationship between the meaning of love, commitment, and relational conflict. The results and discussion show that reducing love to mere emotion weakens the stability of marriage, while understanding love as a spiritual and moral trust strengthens empathy, communication, and conflict resolution mechanisms. The principles of ṣabr, raḥmah, and musyawarah have proven to play an important role in maintaining the resilience of relationships. In conclusion, Islamic marriage values provide a solid and adaptive ethical foundation for building a harmonious, mature, and sustainable family amid the challenges of modernity.